Situating intersectionality politics, policy, and power - Wilson, Angelia R.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
A new generation of political science scholars who are comfortable employing intersectional analysis are emerging and their work hones in directly on the complexity of politics, governance and policy making in an increasingly small, technologically connected, ideologically nuanced, global Public Square.
Keywords: Political science; Comparative politics; Globalization; Sociology; Political sociology; Political Science and International Relations; Political Science; Comparative Politics; Political Sociology; Globalization; Sociology, general